Liposome-coupled antigens are internalized by antigen-presenting cells via pinocytosis and cross-presented to CD8 T cells. - Yuriko Tanaka; Maiko Taneichi; Michiyuki Kasai; Terutaka Kakiuchi; Tetsuya Uchida (PLoS ONE, 2010)
We have previously demonstrated that antigens chemically coupled to the surface of liposomes consisting of unsaturated fatty acids were cross-presented by antigen-presenting cells (APCs) to CD8+ T cells, and that this process resulted in the induction of antigen-specific cytotoxic T lymphocytes. In the present study, the mechanism by which the liposome-coupled antigens were cross-presented to CD8+ T cells by APCs was investigated. Confocal laser scanning microscopic analysis demonstrated that antigens coupled to the surface of unsaturated-fatty-acid-based liposomes received processing at both MHC class I and class II compartments, while most of the antigens coupled to the surface of saturated-fatty-acid-based liposomes received processing at the class II compartment. In addition, flow cytometric analysis demonstrated that antigens coupled to the surface of unsaturated-fatty-acid-liposomes were taken up by APCs even in a 4°C environment; this was not true of saturated-fatty-acid-liposomes. When two kinds of inhibitors, dimethylamiloride (DMA) and cytochalasin B, which inhibit pinocytosis and phagocytosis by APCs, respectively, were added to the culture of APCs prior to the antigen pulse, DMA but not cytochalasin B significantly reduced uptake of liposome-coupled antigens. Further analysis of intracellular trafficking of liposomal antigens using confocal laser scanning microscopy revealed that a portion of liposome-coupled antigens taken up by APCs were delivered to the lysosome compartment. In agreement with the reduction of antigen uptake by APCs, antigen presentation by APCs was significantly inhibited by DMA, and resulted in the reduction of IFN-γ production by antigen-specific CD8+ T cells. These results suggest that antigens coupled to the surface of liposomes consisting of unsaturated fatty acids might be pinocytosed by APCs, loaded onto the class I MHC processing pathway, and presented to CD8+ T cells. Thus, these liposome-coupled antigens are expected to be applicable for the development of vaccines that induce cellular immunity.